Makna Simbolik Dibalik Rumah Adat Masyarakat Waibalun Kecamatan Larantuka Kabupaten Flores Timur - Martinus Irwanto Ishak (Jurnal Spektrum Komunikasi, 2020)
Every culture has its function and meaning. The function and meaning, on the one hand, can be understood in plain view but on the other hand, requires a series of approaches to understanding it well. Of course, the meaning and function of a culture can only be understood in full by the people who use that culture. Furthermore, culture or culture cannot be separated from the language itself. Language becomes one of the determining elements to understand well the nature of a culture. Language can translate the meanings and symbolic meanings of a form or object used in a culture. The Waibalun community in Larantuka Sub-district, East Flores Regency has several symbolic meanings that are expressed in their traditional houses. Therefore, this study specifically examines the symbolic meaning found in traditional houses belonging to the Waibalun community. To answer the purpose of this study, the researcher used a qualitative method with data collection techniques that were interviews and documentation. The results of the research show that the symbolic meaning of the traditional house of the Waibalun community is a determinant of group identity, as a form of religion/respect for ancestors, as a form of appreciation, as a determinant of social status and as a form of livelihood. Besides, the traditional house owned by the Waibalun community has several symbolic meanings that give importance to life and the future of each generation. Surely this symbolic meaning is important and needs to be preserved so that it does not become extinct by the changes of the times.